Hegemoni dalam Film Kupu-Kupu Kertas : Analisis Sosiologi Sastra - Dianatul Qoyyimah; Unaisatuz Zahro; Qotrunnada Anis Salsabila; Ilzamul Hikam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the representation of hegemony in the film Kupu-Kupu Kertas using Antonio Gramsci’s hegemony theory and a literary sociology approach. As a medium of mass communication, film not only conveys stories but also produces and reproduces cultural values, ideologies, and power structures that operate subtly within society. Set against the historical backdrop of 1965, the film portrays ideological clashes between NU/Ansor and the PKI, which affect not only political spheres but also everyday culture, social relations, and moral dynamics that shape the collective consciousness of Javanese society. This research employs a qualitative method with a descriptive approach. Data were collected through content analysis of the film using an observation–note technique to identify scenes, dialogues, and visual symbols related to culture, hegemony, and ideology. The analysis focuses on revealing how dominant values are constructed and negotiated through the representation of characters, narratives, and social traditions portrayed in the film. In conclusion, Kupu-Kupu Kertas not only documents the political tragedy of 1965 but also demonstrates that hegemony operates through subtle mechanisms embedded in culture, morality, and patterns of thought. This study affirms the relevance of Gramsci’s theory in examining literary works and films as social texts that practice power while also opening space for understanding individual resistance to ideological domination.